Two can play at that game: constraining the role of supernova and AGN feedback in dwarf galaxies with cosmological zoom-in simulations - Koudmani, Sophie; Šijački, Debora; Smith, Matthew C. (Arxiv, 2022)
There is growing observational evidence for dwarf galaxies hosting active galactic nuclei (AGN), including hints of AGN-driven outflows in dwarfs. However, in the common theoretical model of galaxy formation, efficient supernova (SN) feedback is the tool of choice for regulating star formation in the low-mass regime. In this paper, we present a suite of high-resolution cosmological dwarf zoom-in simulations relaxing the assumption of strong SN feedback, with the goal to determine whether more moderate SN feedback in combination with an efficient AGN could be a suitable alternative. Importantly, we find that there are sufficient amounts of gas to power brief Eddington-limited accretion episodes in dwarfs. This leads to a variety of outcomes depending on the AGN accretion model: from no additional suppression to moderate regulation of star formation to catastrophic quenching. Efficient AGN can drive powerful outflows, depleting the gas reservoir of their hosts via ejective feedback and then maintaining a quiescent state through heating the circumgalactic medium. Moderate AGN outflows can be as efficient as the strong SN feedback commonly employed, leading to star formation regulation and HI gas masses in agreement with observations of field dwarfs. All efficient AGN set-ups are associated with overmassive black holes (BHs) compared to the (heavily extrapolated) observed BH mass - stellar mass scaling relations, with future direct observational constraints in this mass regime being crucially needed. Efficient AGN activity is mostly restricted to high redshifts, with hot, accelerated outflows and high X-ray luminosities being the clearest tell-tale signs for future observational campaigns.
Version 1 vom 22 Juni 2022, Version 2 vom 2 September 2022
Gesehen am 18.10.2022